PRINCIPLES OF PREPARING THE STUDENTS OF THE "HOUSE OF MERCY" FOR FAMILY LIFE - Kuliyeva Gulchehra Xudoyberdiyevna (American Journals, 2023)
The article explains that the social adaptation of the children of the "kindness house", preparing them for family life is one of the most important tasks of the state and society.